Production of Health Promotion Campaigns at the Kayutangan Heritage Tourism Village, Malang City during the Covid-19 Pandemic - Nia Ashton Destrity; Nilam Wardasari (Warta Pengabdian, 2022)
The Covid-19 pandemic has had a major impact on the economic condition of the local community of the Kayutangan Heritage Tourism Village, Malang City, given their heavy reliance on the influx of tourists. This local community, thus, produced educational activity and health promotion campaigns aimed at increasing awareness, knowledge, and confidence of managers and local communities that the application of health protocols at this tourism village site can prevent the spread of Covid-19. Messages promoting health protocol is produced and disseminated through videos in order to increase the readiness of managers and local communities before this tourism village returns to operations during and after the Covid-19 pandemic. This health promotion video features representatives of tourism village managers as a source of information with the main message of highlighting the potential economic benefits that can be obtained from the commitment to implement health protocols at tourist sites.